Untargeted NMR metabolomics analysis of Ficus racemosa fruit extracts and UHPLC-MS/MS-molecular networking analysis of the active extract - Suil, S. Jasrey Max; Zulaikha Zolkeflee, Nur Khaleeda; Ramli, Nurul Shazini; Mohd Faudzi, Siti Munirah; Tham, Chau Ling; Maulidiani, M.; Jamaludin, Fadzureena; Mediani, Ahmed; Abas, Faridah (Academic Press, 2025)
This study aimed to investigate the effects of drying methods and varying ethanol concentrations on the metabolite composition and biological activity of F. racemosa fruit extracts. Metabolomic analyses were conducted using 1H NMR spectroscopy, while the most active extract was characterized using UHPLC-MS/MS and feature-based molecular networking (FBMN). A total of 40 and 45 metabolites were tentatively identified through NMR and UHPLC-MS/MS analyses, respectively. The biological activity results indicated that the freeze-dried (FD) sample extracted with 100 % ethanol exhibited the highest activity against 2,2-diphenyl-1-picrylhydrazyl radical (DPPH●), as well as α-amylase and α-glucosidase inhibitory activities, with IC50 values of 21.5, 7.5, and 5.9 μg/mL, respectively. These activities were compared with reference standards, where quercetin exhibited SC50 values of 5.6 μg/mL for DPPH scavenging and 7.3 μg/mL for α-glucosidase inhibition, while acarbose showed an IC50 value of 2.0 μg/mL for α-amylase inhibition. Notably, metabolites such as pheophorbide A, phlorizin, bergenin, caffeic acid, luteoloside, chlorogenic acid, vitexin, naringenin, epicatechin, epilupeol, and betulinic acid were identified as major contributors to the observed antioxidant and enzymatic inhibitory activities. This study lays the groundwork for future research into the development of functional foods from F. racemosa fruit, particularly for managing postprandial hyperglycemia in diabetes.